2019
DOI: 10.2147/dddt.s207350
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dextromethorphan and memantine after ketamine analgesia: a randomized control trial</p>

Abstract: Purpose Intravenous ketamine is often prescribed in severe neuropathic pain. Oral N -methyl-D-aspartate receptor (NMDAR) antagonists might prolong pain relief, reducing the frequency of ketamine infusions and hospital admissions. This clinical trial aimed at assessing whether oral dextromethorphan or memantine might prolong pain relief after intravenous ketamine. Patients and methods A multicenter randomized controlled clinical trial included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Results collected at one month showed that dextromethorphan-maintained pain relief induced by ketamine while memantine and placebo increased pain intensity scores. Adverse events included drowsiness and nausea in the dextromethorphan group and dizziness, drowsiness, and constipation in the memantine group [ 37 ]. Another study compared the anti-nociceptive effects of dextromethorphan to placebo and concluded that because dextromethorphan had no intrinsic anti-nociceptive effect in acute pain on healthy skin, the N-methyl-D-aspartate receptor may need to be sensitized by pain for dextromethorphan to be effective [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Results collected at one month showed that dextromethorphan-maintained pain relief induced by ketamine while memantine and placebo increased pain intensity scores. Adverse events included drowsiness and nausea in the dextromethorphan group and dizziness, drowsiness, and constipation in the memantine group [ 37 ]. Another study compared the anti-nociceptive effects of dextromethorphan to placebo and concluded that because dextromethorphan had no intrinsic anti-nociceptive effect in acute pain on healthy skin, the N-methyl-D-aspartate receptor may need to be sensitized by pain for dextromethorphan to be effective [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Psychotic symptoms (hallucinations and delusions) are strongly related to AD-associated cognitive dysfunction, gradually progressing in parallel with disease severity [182]. In addition, symptoms of personality changes, paranoia, hallucinations, cravings, agitation, and changes in appetite may represent a prodromal noncognitive phenotype of risk for dementia [183].…”
Section: Psychotic Disordersmentioning
confidence: 99%
“…In an interesting study by Martin et al ,[ 41 ] the authors randomized 60 patients who were treated for chronic neuropathic pain with 0.4–0.5 mg/kg IV ketamine infusion (over 2 hours) into two groups. In one group, patients received 90 mg/day oral dextromethorphan, in another group the patients received 20 mg/day oral memantine, and in the third group, patients received a placebo, all for 12 weeks.…”
Section: Discussionmentioning
confidence: 99%